Establishing Effective Reserve Components: Lessons Learned from Russia - Tri Yudha Ismanto; Kurniawan Firmuzi Syarifuddin; Irdham Ahmad (Jurnal Indonesia Sosial Sains, 2024)
This research uses a qualitative approach with a case study method to explore lessons that can be drawn from Russia's experience in building an effective military reserve component. The article discusses the importance of establishing a robust and effective reserve force in Indonesia, drawing lessons from Russia's experiences and strategies employed by other nations. It emphasizes the need for a well-structured organization, clear command structures, efficient hierarchies, and regular training programs. The integration of technology and information systems, as well as the provision of welfare and incentives, is also highlighted as essential components for enhancing the effectiveness and readiness of Indonesia's reserve forces. The document also emphasizes the necessity of clear regulations and policies to provide a strong legal framework, ensuring the operational effectiveness and integrity of Indonesia's reserve forces. Additionally, it underscores the importance of integrating reserve components with regular forces through joint exercises, standardized doctrines, and operational procedures. The document concludes by emphasizing the opportunity for Indonesia to design a resilient reserve force by learning from Russia's challenges and strategies employed by other nations, ensuring the creation of a large, effective, well-trained, and deployable reserve force to balance and strengthen the overall national defense system.